Peran Tim Kontekstual Dalam Pelayanan Anak Suku Sunda: Upaya Memperkenalkan Isa Al-Masih Sebagai Satu-Satunya Jalan Keselamatan - Romita Romita; Jose Samaloisa; Markus Landena (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This article discusses the changes experienced by Sundanese children during puberty and the important role of the gospel spirit companion in guiding them. Sundanese society has unique and interesting characteristics that must be observed in its spiritual growth and understanding of the concept of salvation. Although Sundanese society already has good morals and a high spirit of tolerance, to achieve soul salvation according to the concept of Christian salvation, faith in Jesus Christ is needed. Unfortunately, children are often neglected in evangelism, and the lack of service to them is a problem that must be overcome. Therefore, the "Child Reureuh" activity was held to provide an understanding of the teachings of the Bible and the concept of salvation to Sundanese children. The research method used was qualitative descriptive, and this activity was carried out at Wisma Karang Tumaritis, Parompong, West Bandung. Involving children in evangelism is expected to build a strong foundation of faith from an early age and have a positive impact on their lives. This article aims to explore the role of contextual teams in introducing the love of Jesus Christ to Sundanese children and its impact on their ministry, as well as provide a comprehensive overview of contextual approaches in religious and humanitarian contexts.